Efficient regio- and stereoselective access to novel fluorinated β-aminocyclohexanecarboxylates - Kiss, Loránd (Beilstein-Institut, 2013)
A regio- and stereoselective method has been developed for the synthesis of novel fluorinated 2-aminocyclohexanecarboxylic acid derivatives with the fluorine attached to position 4 of the ring. The synthesis starts from either cis- or trans-β-aminocyclohex-4-enecarboxylic acids and involves regio- and stereoselective transformation of the ring C–C double bond through iodooxazine formation and hydroxylation, followed by hydroxy–fluorine or oxo–fluorine exchange.